Horn core cancer in a Zebu cow, imported to Brazil - Rezende, Ana Margarida Langenegger de; Neves, Paulo de Tarso (Pesquisa Agropecuaria Brasileira, 2014)
Horn cancer or horn core cancer was diagnosed in a 15 year old Guzera cow, which was imported to Brazil from Índia 7 years ago. This is a common disease of Zebu cattle in Índia, where its occurrence causes considerable losses in cattle. The case in question occurred near Barretos, in the state of São Paulo. Horn cancer is known so far to occur only in imported Gir and Guzera cattle. Softening and deviation of the left horn, and destruction of the horn core and adjacent cranial bones was observed. Alter surgical treatment recurrence of the neoplasm was observed. Histopathological examination of tissue sections revealed a squamous keratinizing cell carcinoma.